Dampak Return on Investment, Debt to Equity Ratio, Net Profit Margin terhadap Nilai Tobin’s Q - Sumarso Sumarso; Pahman Habibi; Fikri Hidayat; Arif Widodo Nugroho (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This research was conducted with the intention of knowing how the impact is generated by Return on Investment, Debt to Equity Ratio and Net Profit Margin on Firm Value as measured by Tobin's Q ratio. The research was conducted on the Jakarta Islamic Index 70 companies listed on the Indonesia Stock Exchange. The method used in this research is quantitative method. Where in this study we use the numbers obtained from the calculation of the ratios carried out. obtained from the ratio calculations carried out. In addition, we also adopted purposive sampling method to limit the research. The data obtained in this research. The research findings show that there is a negative impact of Return on Investment. show that there is a negative impact caused by Return on Investment and Debt to Equity Ratio to Tobin's Q Value. While Net Profit Margin has a positive impact on Tobin's Q Value. Simultaneously overall independent variables in this study were also found to have an impact on the dependent variable. dependent variable. As well as in correlation, there is a correlation of 27.6 percent independent variables to the dependent variable. While the rest, which is 72.4 percent may be influenced by other variables not tested in this study.